The Concept of Science Covers Everything: A Review of the Philosophy of Science - Astri Sulastri; Gita Amelia; Parmi; Tamsik Udin (Penerbit Hellow Pustaka, 2026)
Science plays a fundamental role in the development of human civilization. It is not merely understood as a collection of empirical facts, but as a systematic body of knowledge constructed through philosophical reflection. This article aims to examine the concept of science from the perspective of the philosophy of science by emphasizing ontological, epistemological, and axiological dimensions as well as shifts in scientific paradigms. This study employs a qualitative approach using library research methods. Data analysis was conducted through content analysis and conceptual synthesis of relevant literature. The findings indicate that science is a rational, systematic, and value-laden intellectual activity. This study highlights the importance of a holistic understanding of science so that scientific development remains oriented toward ethical and humanitarian values, particularly in the context of Islamic higher education.